PET Study of Sphingosine-1-Phosphate Receptor 1 Expression in Response to Vascular Inflammation in a Rat Model of Carotid Injury - Hui Liu PhD, MD; Hongjun Jin PhD; Xuyi Yue PhD; Junbin Han PhD; Pamela Baum SRS; Dana R. Abendschein PhD; Zhude Tu PhD (Molecular Imaging)
Sphingosine-1-phosphate receptor (S1PR) activation plays a key role in vascular inflammatory response. Here, we report in vivo validation of [ 11 C]TZ3321, a potent S1PR1 radioligand, for imaging vascular inflammation in a rat model of carotid injury. The right common carotid artery of male adult Sprague-Dawley rats was injured by balloon overinflation that denuded the endothelium and distended the vessel wall. Animals received a 60-minute micro-positron emission tomography (micro PET) scan with [ 11 C]TZ3321 at 72 hours after injury. Ex vivo autoradiography was also conducted. The expression and cellular location of S1PR1 were examined by immunohistological analysis. Three-dimensional (3D) reconstruction of the first 100-second microPET/computed tomography (CT) image indicated the location of bilateral common carotid arteries. [ 11 C]TZ3321 displayed significantly higher accumulation (standardized uptake values: 0.93 ± 0.07 vs 0.78 ± 0.09, n = 6, P = .001) in the injured carotid artery than in the contralateral side. Increased tracer uptake in the injured artery was confirmed by autoradiography (photostimulated luminescence measures: 85.5 ± 0.93 vs 71.48 ± 6.22, n = 2). Concordantly, high S1PR1expression was observed in infiltrated inflammatory cells in the injured artery. Our studies demonstrate [ 11 C]TZ3321 microPET is able to detect the acute upregulation of S1PR1 expression in inflamed carotid artery. Therefore, [ 11 C]TZ3321 has potential to be a PET radiotracer for detecting early inflammatory response and monitoring therapeutic efficacy of vascular inflammation.